Our (water) ways recovering our past to reclaim our future - Uys, Julia (School of Architecture, Planning and Geomatics, 2025)
Cape Town - a picturesque city located between an iconic mountain range and the glistening bay. At its forefront framed by Table Mountain, the city lies nestled within bowl shaped by mountains on either side with the wide expanse of the ocean at its feet. This image of Cape Town commands the imagination when envisaging the city and used as a key landmark in orientating the individual within its urban environment. Despite this, a growing spatial paradox is emerging; a paradox of being within yet without. The vantage point from which this mental photograph is understood, represents only a two-dimensional face value view of its rich personality and a very different city to the realities on the ground. Today, the city centre is a confusing and chaotic space; on the surface a dizzying cacophony of speeding lights and towering structures, the white noise of sirens whirring within a visual-ly drab, spatially fragmented and harsh hop-scotch-like environment. And yet this reality only illustrates a part of the story, the rest buried underground in tunnels, ancient riverbeds, springs and seabed artifacts. A rich collection of memories closely tied to the character of basin the city finds itself nestled in, hidden from sight. In this emerging environment, the narrative of water and its visual reminders (both mountain and sea) have been lost. Those remaining are isolated, lacking in understanding within the current context, this is the fractured characterless reality pedestrians must navigate, indicative of the complete disconnect between inhabitants and this unique context. This thesis argues that by re-hydrating the city, the connections to people, space and place can be restored and reinvigorated